PENGETAHUAN INISIASI MENYUSUI DINI BERPENGARUH TERHADAP PROSES LAKTASI PADA IBU NIFAS - Erna Mesra; Jujum Rumdasih; Fauziah Fauziah (Poltekkes Kemenkes Jakarta III, 2013)
The Initiation of early give a suck is very useful for the mother and baby. About 30.000 babies in Indonesia can be saved every year if this program can be implemented in every mother who get childbirth to her baby. The purpose of this research is to know the factors which can influence the initiation of early give a suck, there is lactation process relationship with IMD of age, education, parity and supporting of family and also supporting of medical manpower of the processes of lactation. The research use cross sectional design. Sample of 119 respondents of univariat, bivariat and multivariat with logistics regression. The result of research is 90,8% of mother of childbirth who is doing the initiation of early give a suck. Process of lactation/ its influent of lactation about first 3 days after birth that be experienced by the mother who is doing IMD about 87%. There is a meaning relation between education , knowledge, supporting from family/husband and supporting from the medical manpower to the process of lactation, the dominant variable is the knowledge with high relation can be looked from the result of grade about OR 12 694 CI 95% (2694-59372) This matter has the meaning with the good knowledge that have the opportunity in doing IMD and get the fluent lactation process in the third day after birth is about 12694 times be compared with the less knowledge.